Change hydrogen-peroxide forming NADH oxidase substrate specificity by site directed mutagenesis - Choong, Carmen. (2009)
Site directed mutagenesis is a molecular biology technique used to determine the biological roles of many proteins. It complements computational techniques such as protein docking, where the structure of a complex between protein and its substrate is predicted based on the independently crystallized structures of the components through X-ray crystallization. Site directed mutagenesis involves a desired mutation at a defined site in a DNA molecule, and it is the molecular technique investigated in this research.